Language Acquisition Ability of Children Who Experience Speech Delays (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
Language acquisition and learning by children is one of the greatest achievements and successes for humanity. Therefore, a lot of attention is paid to this issue and it is analyzed in depth. Learning and speaking a language is an interdependent process. Fullness of a person, i.e., biological maturity, is manifested through the acquisition of language under the influence of the environment and the correct formation of speech skills in relation to age. However, not all children have the same level, some children have a deficiency in terms of biological development, and this does not affect the level of language acquisition. This problem is very interesting and important in the analysis of changes in language factors of children lagging behind in speech development. The results of the research show that the incorrect and incomplete pronunciation of certain words by the child's speech, contrary to the expected goal, led to attention to additional problems and analyzed the solutions. A child who is behind in speech activity has difficulties in pronouncing words and expressing them, and solving them requires a lot of work.